Kekerasan Verbal Siswa dan Penanganannya melalui Layanan Bimbingan dan Konseling: Studi Kasus Klinis di MAN 2 Bulukumba - Amanah Fitriyah; Nur Fadhilah Umar; Aswar Aswar (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Verbal violence among students is a serious psychosocial problem in schools because it may disrupt interpersonal relationships, emotional development, and students’ psychological well-being. Although verbal aggression is often perceived as ordinary teasing or joking, repeated exposure may lead to anxiety, fear, decreased self-confidence, and social withdrawal among victims. This study aimed to describe the forms of verbal violence, its contributing factors, its psychological impact on victims, and the efforts made to address it through guidance and counseling services at MAN 2 Bulukumba. A qualitative approach with a clinical case study design was employed. The participants consisted of MF as the perpetrator, AR as the victim, the school counselor, parents, and peers. Data were collected through in-depth interviews, observation, and documentation, and were analyzed using the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The findings revealed that MF’s verbal violence appeared in the form of harsh words, ridicule, insults, and emotionally uncontrolled speech that had developed into a habitual behavior. The contributing factors included poor emotional regulation, impulsivity, limited parental supervision, and a peer environment that tolerated harsh language. The impact on the victim included reduced self-confidence, anxiety, fear, and social withdrawal. The handling process involved guidance and counseling services based on Cognitive Behavior Therapy (CBT), role playing, and collaboration with parents and school stakeholders. These findings highlight the importance of structured, collaborative, and sustainable counseling interventions in preventing and addressing verbal violence in schools. The study provides practical implications for school counselors in developing socio-emotional guidance programs, strengthening emotional regulation, and fostering a respectful, empathetic, safe, and inclusive school communication culture.